2019
DOI: 10.4132/jptm.2019.07.15
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of Mongolian Diffuse Gliomas According to the Revised 2016 World Health Organization Central Nervous System Tumor Classification

Abstract: Background: The 2016 World Health Organization (WHO) classification of central nervous system (CNS) tumors has been modified to incorporate the IDH mutation and 1p/19q co-deletion in the diagnosis of diffuse gliomas. In this study, we aimed to evaluate the feasibility and prognostic significance of the revised 2016 WHO classification of CNS tumors in Mongolian patients with diffuse gliomas. Methods: A total of 124 cases of diffuse gliomas were collected, and tissue microarray blocks were made. IDH1 mutation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In agreement with recent molecular reclassification studies, we showed a distinct prognostic segregation of glioma subtypes with the 2016 WHO classification as well as a prognostic significance of IDH mutation over histological tumour grade [26][27][28][29]47]. Interestingly, however, was the significant prognostic difference found in OS between WHO grade II and III IDH-mutant astrocytoma patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with recent molecular reclassification studies, we showed a distinct prognostic segregation of glioma subtypes with the 2016 WHO classification as well as a prognostic significance of IDH mutation over histological tumour grade [26][27][28][29]47]. Interestingly, however, was the significant prognostic difference found in OS between WHO grade II and III IDH-mutant astrocytoma patients.…”
Section: Discussionsupporting
confidence: 91%
“…[26], Orhirjav et al . [27] and Brito et al . [28] also reported oligodendroglial tumours and WHO grade II/III astrocytomas as the main targets of reclassification, whereas the French nationwide POLA cohort (cohort of high‐grade glioma with an oligodendroglial component) [29] showed most frequent classification changes among astrocytomas and glioblastomas, but less common re‐classification of oligodendroglial tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of the glioma for IDH mutations was recommended as a required molecular testing for "integrated diagnosis" in the 2016 revised WHO classification of tumors of the central nervous system. In addition to histologic grade, the clinical outcome needs to be described within these IDH categories (9). Current diagnostic, prognostic, and predictive considerations also depend on IDH status (10).…”
Section: Discussionmentioning
confidence: 99%
“…For histopathological examination, 3-μm-thick sections were stained with H&E. Histological diagnosis and grading were done according to the WHO classification of central nervous system tumors. 15,16 based on cellularity, pleomorphism, number of mitoses per 10 high-power field (HPF), presence or absence of microvascular proliferation, and necrosis.…”
Section: Histopathological Examinationmentioning
confidence: 99%